TINGKAT PENGETAHUAN PETANI TENTANG BUDIDAYA JERUK SIOMPU DI DESA WAINDAWULA KECAMATAN SIOMPU KABUPATEN BUTON SELATAN - Siti Nur Rahma; Sukmawati Abdullah; Tjandra Buana (Universitas Halu Oleo, 2022)
This study aims to determine the level of farmers' knowledge about Siompu Orange Cultivation in Waindawula Village, Siompu District, South Buton Regency. This research was conducted in Waindawula Village, Siompu District, South Buton Regency from February 2022 to July 2022. The location of the research was determined purposively (purposively) with the consideration that Waindawula Village is one of the villages where most of the people cultivate Siompu oranges. The population in this study were all farmers cultivating Siompu oranges in Waindawula Village, Siompu District, South Buton Regency as many as 30 people. Sampling method is done by the census method. The results of this study can be concluded that the level of farmers' knowledge about Siompu Orange Cultivation in Waindawula Village, Siompu District, South Buton Regency is categorized as moderate, meaning that farmers do not yet have sufficient knowledge to cultivate Siompu Oranges, so farmers are expected to continue learning to improve their knowledge. Based on the results of the study, it can be concluded that the level of farmer knowledge about Siompu orange cultivation in Waindawula Village, Siompu District, South Buton Regency can be concluded in the high category. Suggestions that can be conveyed to the government are expected to be able to provide innovation and the right technology for farmers to increase Siompu orange production which will lead to increasing welfare by taking into account the conditions, and it is hoped that Siompu Orange Farmers in Waindawula Village, Siompu District, South Buton Regency can continue to learn to increase their knowledge of Siompu Orange cultivation by following existing technological developments so as to improve welfare